2019
DOI: 10.5114/pcard.2019.92713
|View full text |Cite
|
Sign up to set email alerts
|

Maximal velocity of fetal pulmonary venous blood flow

Abstract: Introduction: Doppler imaging of foetal pulmonary veins plays a crucial role in prenatal cardiology centres. Therefore, we established reference ranges for maximal fetal pulmonary venous blood flow velocity for our unit. Material and methods: A database of fetal ultrasound and echocardiographic examinations was analysed retrospectively. Healthy fetuses with no evidence of heart defect or any abnormality at the time of examination were selected as a study group. Fetuses with functional or morphological anomalie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Pulmonary vein blood flow velocity at the level of their connection to the left atrium plays a role in shape and movement of FO, in normal and abnormal conditions [12]. In normal fetuses with advancing gestational age, there is an increase in pulmonary blood flow [13], so one might expect a decrease in the FO index, as it should be closed postnatally [14]. On the other hand, it may suggest that despite an increased pulmonary blood flow in fetal lungs, there is still preserved functional stability at the atrial level.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary vein blood flow velocity at the level of their connection to the left atrium plays a role in shape and movement of FO, in normal and abnormal conditions [12]. In normal fetuses with advancing gestational age, there is an increase in pulmonary blood flow [13], so one might expect a decrease in the FO index, as it should be closed postnatally [14]. On the other hand, it may suggest that despite an increased pulmonary blood flow in fetal lungs, there is still preserved functional stability at the atrial level.…”
Section: Resultsmentioning
confidence: 99%
“…That is why many scientists try to rule out noninvasive methods to reach the same or even better predicting results. For this purpose, fetal echocardiography as widely available tools is used in normal and complicated by fetal and maternal diseases pregnancy to assess proper fetal lung development 2–14 …”
Section: Figurementioning
confidence: 99%
“…Of them maternal inflammation plays a role, regardless of its etiology: bacterial or viral infection, autoimmune disease, severe hypoxia and injury. Physiologically with gestation resistance decrease in fetal pulmonary vasculature 7 . Impaired vascular and pulmonary tissue growth disenable blood pressure to decrease, what could be mirrored by shorter pulmonary artery AT in echocardiographic examination.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have concluded that the assessment of the atrial septum is useful (29,31). Pulmonary flow is growing during the pregnancy which may cause the restriction of the FO (32,33). Therefore, the assessment of the FO in the twentieth weeks of pregnancy could be insufficient to accurately predict the newborns' condition after delivery (22,33).…”
Section: Critical Vs Planned D-tgamentioning
confidence: 99%